Sexploitation: sexual profiling and the illusion of gender - Alexandre, Michèle (Routledge series on identity politics, 2014)
"Michèle Alexandre defines "sexploitation" as the perpetuation of myths and stereotypical notions regarding men and women in order to further an agenda of oppression and subordination in certain spheres of society. The most popular means through which this sexploitation is achieved is through a method Alexandre coins as "sexual profiling." Alexandre argues that sexual profiling ultimately stifles the growth of our society by creating inefficient as well as oppressive systems, and that its eradication can help increase the productivity as well as the morale of society. Alexandre opens the book by exploring in detail the various ways in which normative views of gender are constructed and perpetuated through media and societal norms. She then focuses on the ways in which recent legal opinions and developments contribute to perpetuate these restrictive and oppressive norms. Finally, Alexandre outlines a plan to help eliminate the presence of these destructive norms and attitudes from different sectors of society.Sexploitation from the Newsroom to the Courtroom examines how sexual profiling represses, oppresses, and hinders various aspects of life for both genders, and explores the ways in which the law and the community can help eradicate the practice of sexual profiling"--